Pengaruh Literasi Digital, Motivasi Kerja, dan Kesempatan Bimbingan Karir terhadap Kesiapan Kerja Generasi Z - Fuada, Dyah Tuhrotul; Anggraeni, Putri Ayunda; Puspita, Adhelia Cahya; Firdaus, Vera (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of digital literacy, work motivation, and career guidance opportunities on Generation Z's work readiness. Generation Z, born between 1997 and 2012, has unique characteristics because they grew up in the digital era, but data shows that they face challenges in work readiness. The research method used was quantitative with data collection through questionnaires distributed to 110 respondents from various backgrounds. Data analysis was conducted using validity and reliability tests, classical assumption tests, and multiple linear regression with the help of SPSS. The results showed that digital literacy and work motivation had a significant influence on work readiness, while career guidance also contributed, although in a smaller proportion. This study provides recommendations to improve digital literacy and work motivation as strategic steps in preparing Generation Z for the increasingly competitive world of work.